Effects of Ramadan observance on dietary intake and body composition of adolescent athletes: Systematic Review and Meta-Analysis - Trabelsi, Khaled; Engel, Florian (Nutrients, 2020)
To evaluate the effects of Ramadan observance on dietary intake, body mass and body composition of adolescent athletes (design: systematic review and meta-analysis; data sources: PubMed and Web of Science; eligibility criteria for selecting studies: single-group, pre-post, with or without control-group studies, conducted in athletes aged <19 years, training at least 3 times/week, and published in any language before 12 February 2020). Studies assessing body mass and/or body composition and/or dietary intake were deemed eligible. The methodological quality was assessed using ‘QualSyst’. Of the twelve selected articles evaluating body mass and/or body composition, one was of strong quality and eleven were rated as moderate. Ten articles evaluated dietary intake; four were rated as strong and the remaining moderate in quality. Continuation of training during Ramadan did not change body mass from before to the first week (trivial effect size (ES) = −0.011, p = 0.899) or from before to the fourth week of Ramadan (trivial ES = 0.069, p = 0.277). Additionally, Ramadan observance did not change body fat content from before to the first week (trivial ES = −0.005, p = 0.947) and from before to the fourth week of Ramadan (trivial ES = -0.057, p = 0.947). Lean body mass remained unchanged from before to the fourth week of Ramadan (trivial ES = −0.025, p = 0.876). Dietary data showed the intake of energy (small ES = -0.272, p = 0.182), fat (trivial ES = 0.044, p = 0.842), protein (trivial ES = 0.069, p = 0.720), carbohydrate (trivial ES = 0.075, p = 0.606) and water (trivial ES = −0.115, p = 0.624) remained essentially unchanged during as compared to before Ramadan. Continued training of adolescent athletes at least three times/week during Ramadan observance has no effect on body mass, body composition or dietary intake.
Gesehen am 26.10.2020